Penerapan Terapi Psikologis dalam Menurunkan Tingkat Depresi pada Pasien Hemodialisis: Literature Review - Dewiyanti Toding; Masfuri Masfuri; Sri Yona (FORIKES, 2021)
The prevalency of hemodialysis patient with depression was high but only a few of patients who experienced the symptoms of the depression were diagnosed and treated. Therefore, the study and treatment of depression is one of the highest priorities in health care in the hemodialysis unit. Although psychological therapy has been widely implemented in hemodialysis patients who were depressed, the effectiveness from psychological therapy particularly applied to hemodialysis patients in Indonesia has not been certainty. This article was intended to assess the effectiveness of psychological therapy on a decline in depression levels in hemodialysis patients. The study of the article was a literature study obtained through data retrieval on four online databases of Pubmed, Ebsco, Cocharane and Scopus with the inclusion criteria have randomized control trial (RCT) designs, full text, published in 2015-2020, and in English. In the search, there were 219 articles found later in the review on abstract according to the research purpose that followed 8 selected articles after quality assessment using Critical Appraisal Skills Programme guide. The 4 types of psychological therapy were cognitive behavioral therapy, psychoeducation, hemodialysis self-management and hope therapy are potentially applied in Indonesia. These modifications and combinations of interventions could be suggested as to further research to improve th effectivities of phisicological therapy on hemodyalisis patients who were depressed. Keywords: cognitive behavioral therapy; hemodialysis; self-management; hope therapy; intervention; psychoeducation ABSTRAK Prevalensi pasien hemodialisis yang mengalami depresi masih tinggi tetapi hanya sebagian kecil yang gejala depresinya didiagnosis dan ditangani. Oleh karena itu, kajian dan penanganan terhadap depresi merupakan salah satu prioritas utama dalam pelayanan kesehatan di unit hemodialisis. Meskipun terapi psikologis telah banyak digunakan pada pasien hemodialisis yang mengalami depresi, tetapi belum ada kepastian efektifitas dari terapi psikologis terutama untuk bisa diterapkan pada pasien hemodialisis di Indonesia. Artikel ini bertujuan untuk menilai efektifitas terapi psikologis terhadap penurunan tingkat depresi pada pasien hemodialisis. Penelitian artikel ini mengunakan kajian literatur yang diperoleh melalui pencarian pada 4 database online yaitu Pubmed, EBSCO, Cocharane dan Scopus dengan kriteria inklusi memiliki desain Randomized Control Trial (RCT), full text, dipublikasi tahun 2015-2020, dan berbahasa Inggris. Dalam pencarian ditemukan ada 219 artikel, kemudian di telaah yang sesuai dengan tujuan penelitian dan selanjutnya diperoleh 8 artikel terpilih setelah dilakukan penilain kualitas dengan menggunakan panduan Critical Appraisal Skills Programme (CASP). 4 jenis terapi psikologis yaitu cognitive behavioral therapy, psychoeducation, hemodialysis self- management dan hope therapy berpotensi untuk diterapkan di Indonesia. Modifikasi dan kombinasi dari berbagai intervensi ini disarankan untuk dilakukan pada penelitian selanjutnya untuk lebih meningkatkan efektivitas terapi psikologis pada pasien hemodialisis yang mengalami depresi. Kata kunci: cognitive behavioral therapy; hemodialisis; self-management; hope therapy; intervensi; psychoeducation